PENGEMBANGAN KOMIK PEMBELAJARAN PERUBAHAN IKLIM BERBASIS INQURI UNTUK MEMBENTUK SIKAP KEPEDULIAN DAN TANGUNG JAWAB MURID - Roswita Lioba Nahak; Selfiana Ndapa Lawa (FKIP Universitas Citra Bangsa, 2026)
Abstract. This study aims to develop an inquiry-based climate change learning comic that is valid, practical, and effective for use by teachers and students in the learning process. The research employed a Research and Development (R&D) approach using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used in this study included validation and practicality sheets. The validation instruments were assessed by three validators: a content expert, a language expert, and a media expert, while the practicality instrument was completed by practitioners. The results of the validity test conducted by the validation team showed an average validity score of 87%, categorized as very valid. Meanwhile, the average score of the practicality test conducted by teachers and students was 84.5%, categorized as very practical. The effectiveness test indicated effective student learning outcomes, with an average achievement score of 90%. Furthermore, the results of the student response questionnaire showed an average percentage of students’ attitudes and environmental awareness of 80%, which falls into the good category. Therefore, it can be concluded that the developed inquiry-based climate change learning comic is highly valid, practical, and effective, and can be integrated into the IPAS subject.Keywords: Learning Comics, Inquiry-Based Learning, Climate Change Education Abstrak. Penelitian ini bertujuan untuk menghasilkan komik pembelajaran perubahan iklim berbasis inquiri yang valid, praktis dan efektif yang dapat digunakan guru dan murid dalam kegiatan pembelajaran. Jenis penelitian menggunakan Research dan Development (R&D) dengan model pengembangan ADDIE yang terdiri dari lima tahapan: Analisis, Desain, Pengembangan, Pelaksanaan dan Evaluasi. Instrumen yang dipakai menggunakan lembar validasi dan praktikalitas. Instrumen penilaian divalidasi oleh tiga validator yakni validator isi, validator bahasa dan validator media. Sedangkan lembar praktikalitas ditentukan oleh praktisi. Hasil uji validitas oleh tim validator menunjukan perolehan nilai rata-rata validitas sebesar 87 % dengan kategori sangat valid sedangkan nilai rata-rata hasil uji praktikalitas oleh guru dan murid sebesar 84,5% dikategorikan sangat praktis. Uji efektivitas menunjukkan ketuntasan murid terhadap hasil belajar murid yang efektif dengan perolehan rata-rata skor sebesar 90%. Selanjutnya hasil angket respon murid diperoleh hasil rata-rata persentasi sikap dan kepedulian murid sebesar 80% pada kategori baik . Dengan demikian dapat disimpulkan bahwa hasil produk pengembangan komik pembelajaran perubahan iklim berbasis inquiri sangat valid, praktis dan efektif serta dapat diitegrasikan dalam mata pelajaran IPAS.Kata Kunci: Komik Pembelajaran, Inquiri, Pendidikan Perubahan Iklim.